2021
DOI: 10.1111/dom.14365
|View full text |Cite
|
Sign up to set email alerts
|

Titratable fixed‐ratio combination of basal insulin plus a glucagon‐like peptide‐1 receptor agonist: A novel, simplified alternative to premix insulin for type 2 diabetes

Abstract: Despite novel therapeutic options, many people with type 2 diabetes (T2D) do not achieve their HbA1c targets. Given the progressive nature of T2D, many individuals not controlled with oral therapy will require advancement to injectable therapy using either a glucagon-like peptide-1 receptor agonist (GLP-1 RA), recently recommended as a first option, or traditionally a basal insulin. However, premix insulins remain frequently used, either as initial injectable therapy or as intensification from basal insulin. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
1
7
0
3
Order By: Relevance
“…The MOSAIc study of 18 countries showed that about 30% of people with T2DM taking insulin were using premix insulin globally, and the percentage was 67% in China (11). However, several real-world studies have shown that glycemic control remains unsatisfactory 6-12 months after initiating or switching therapy with premix insulin (12)(13)(14). The reasons of poor glycemic control in patients on premix insulin include fear of weight gain and hypoglycemia and the need for frequent selfmonitoring of blood glucose (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MOSAIc study of 18 countries showed that about 30% of people with T2DM taking insulin were using premix insulin globally, and the percentage was 67% in China (11). However, several real-world studies have shown that glycemic control remains unsatisfactory 6-12 months after initiating or switching therapy with premix insulin (12)(13)(14). The reasons of poor glycemic control in patients on premix insulin include fear of weight gain and hypoglycemia and the need for frequent selfmonitoring of blood glucose (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, several real-world studies have shown that glycemic control remains unsatisfactory 6-12 months after initiating or switching therapy with premix insulin (12)(13)(14). The reasons of poor glycemic control in patients on premix insulin include fear of weight gain and hypoglycemia and the need for frequent selfmonitoring of blood glucose (12). FGM may be a good solution to these problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high proportion of people with suboptimal controlled T2D display low rates of achieving acceptable glycaemic control whilst receiving these insulin preparations [46,47]. Premixed insulins also carry an increased risk of weight gain and hypoglycaemia compared with other strategies, such as an FRC [48], and individuals often do not experience any additional clinical benefit when switched to premixed preparations from other insulin regimens [49][50][51].…”
Section: Reducing Medication Without Compromising Safetymentioning
confidence: 99%
“…In this regard, fixed-ratio combinations (FRCs) of basal insulin and glucagon-like peptide 1 receptor agonists (GLP-1 RAs) provide a novel alternative. The FRCs-insulin degludec/liraglutide and insulin glargine/lixisenatide-have a more physiological mode of action, as they target both postprandial and prandial glucose levels [50][51][52]. The FRCs might be an option for initiation in individuals with high postprandial glycemic surges, which are typically observed in the Asian population [30,51,52].…”
Section: Current Options For Insulin Initiation and Dosingmentioning
confidence: 99%